The origin and development of the oasis landscape of al-ʿAin (UAE) - Power, Timothy; Sheehan, Peter (Proceedings of the Seminar for Arabian Studies, 2012)
This paper constitutes a brief review of the archaeological evidence for the origin and development of the oasis landscape of al-ʿAin, prompted by the inscription of the cultural sites of al-ʿAin on the list of UNESCO World Heritage sites in June 2011. For the purposes of this review our definition of an oasis is based on the existing form found in al-ʿAin, characterized by artificially watered sunken basins supporting intensive palm cultivation. The recent excavations by the Abu Dhabi Authority for Culture and Heritage (ADACH) at the Bayt Bin ʿĀtī al-Darmakī produced the most complete archaeological sequence to have been published from the al-ʿAin (Buraimi) oasis. This offers fresh insights into the ceramic chronology of al-ʿAin which can be applied to the developing landscape. The distribution of known settlement sites and residual ceramics suggests that from the Bronze Age onwards, there appears to have been a general tendency of settlement to expand from the north-east to the south-west of al-ʿAin. Although date stones were found in Bronze and Iron Age settlements, we note that no evidence for palm cultivation has been found prior to the late Islamic period. The concept of prehistoric date-palm oases, which appears in the archaeological literature, represents a retrospective and a historic projection of the present oasis landscape into the remote past. We present new evidence from Bin ʿĀtī and other sites excavated by AD ACH in the al-ʿAin oases, which suggests that many of the sunken date-palm gardens and associated underground water channels (aflāj, sg.falaj) were cut in the late Islamic period, and that the present oasis landscape was a product of this activity. Archaeological and historical evidence is then brought together to trace the development of the oases through the late Islamic period to the present day.